Multislice algorithms revisited: solving the Schrödinger equation numerically for imaging with electrons - Wacker, Christian; Schröder, Rasmus R. (Ultramicroscopy, 2015)
For a long time, the high-energy approximation was sufficient for any image simulation in electron microscopy. This changed with the advent of aberration correctors that allow high-resolution imaging at low electron energies. To deal with this fact, we present a numerical solution of the exact Schrödinger equation that is novel in the field of electron microscopy. Furthermore, we investigate systematically the advantages and problems of several multislice algorithms, especially the real-space algorithms.
Available online 17 December 2014
Gesehen am 10.08.2017